2017
DOI: 10.1128/jvi.01081-16
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Damage during Dengue Virus Infection: Making Sense of DNA by cGAS

Abstract: Early sensing of viral components or infection-induced tissue damage is a prerequisite for the successful control of pathogenic viruses by the host innate immune system. Recent results from our laboratory show how immune cells use the DNA-sensing machinery to detect intracellular damage generated early during infection by an RNA virus, namely, dengue virus (DENV). Conversely, we found that DENV can efficiently dismantle this sensing mechanism by targeting the cyclic GMP-AMP synthase (cGAS) and the stimulator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Through association with the N-terminal CARD-like domain and the C-terminal transmembrane domain of mitochondrial anti-viral signaling protein (MAVS), DENV NS4A protein prevents MAVS binding to retinoic acid-inducible gene I, and suppresses the downstream activation of IRF3 and NF-jB as well as IFN production [36]. These mechanisms mediated by different DENV non-structural proteins are proposed to affect the mitochondrion-ER interaction to avoid the accumulation of DENV proteins in that organelle and to minimize mtDNA leakage into the cytoplasm [38]. Furthermore, DENV NS4B protein can induce mitochondria elongation that physically interacts with convoluted membranes in the ER-mitochondria interface, promotes viral replication, and inhibits IFN responses [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through association with the N-terminal CARD-like domain and the C-terminal transmembrane domain of mitochondrial anti-viral signaling protein (MAVS), DENV NS4A protein prevents MAVS binding to retinoic acid-inducible gene I, and suppresses the downstream activation of IRF3 and NF-jB as well as IFN production [36]. These mechanisms mediated by different DENV non-structural proteins are proposed to affect the mitochondrion-ER interaction to avoid the accumulation of DENV proteins in that organelle and to minimize mtDNA leakage into the cytoplasm [38]. Furthermore, DENV NS4B protein can induce mitochondria elongation that physically interacts with convoluted membranes in the ER-mitochondria interface, promotes viral replication, and inhibits IFN responses [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DENV NS4B protein can induce mitochondria elongation that physically interacts with convoluted membranes in the ER-mitochondria interface, promotes viral replication, and inhibits IFN responses [35]. These mechanisms mediated by different DENV non-structural proteins are proposed to affect the mitochondrion-ER interaction to avoid the accumulation of DENV proteins in that organelle and to minimize mtDNA leakage into the cytoplasm [38].…”
Section: Discussionmentioning
confidence: 99%
“…432 As will be discussed below, flaviviruses deploy countermeasures to many immune mechanisms, and in this case DENV inactivates both cGAS and its downstream effector STING countering their activation of interferon-signaling pathways. 432,433 …”
Section: Antiviral Factorsmentioning
confidence: 99%
“…Several studies have shown that some retroviruses including HIV, murine leukemia virus, and simian immunodeficiency virus can induce a type I IFN response due to recognition of reverse-transcribed DNA by cGAS and subsequent production of cGAMP (Gao et al, 2013a; Lahaye et al, 2013; Rasaiyaah et al, 2013). DENV can antagonize STING signaling by utilizing viral NS2B3 proteases to bind and cleave human STING although this cleavage does not occur in mouse or nonhuman primate STING (Aguirre and Fernandez-Sesma, 2017; Aguirre et al, 2012; Stabell et al, 2018; Yu et al, 2012). HCV has also been shown to antagonize STING signaling, highlighting the multifaceted role of STING in pathogen evasion beyond direct DNA sensing through cGAS (Ding et al, 2013; Maringer and Fernandez-Sesma, 2014; Moriyama et al, 2007; Nitta et al, 2013).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%